VALUES FROM THE PERSPECTIVE OF THE KAILI TRIBE TO BUILD A CULTURE OF PEACE - Ratu, Bau; Puswiartika, Dhevy; Amiruddin, Amiruddin; Nurwahyuni, Nurwahyuni; Misnah, Misnah; Buchori, Sahril (JOMSIGN: Journal of Multicultural Studies in Guidance and Counseling, 2024)
This research aims to describe the values of peace based on the perspective of the Kaili tribal community. The scope of the study includes the values of peace in the Nosarara Nosabatutu philosophy possessed by the Kaili tribe as a basis for building a culture of peace. Nosarara Nosabatutu means unity and family, which is one of the local wisdom values of the Kaili tribe. The research method used is an ethnographic study that describes the peaceful values of the Kaili tribe. Data collection methods include in-depth interviews, documentation, and literature study. There were 3 participants in this research from the Kaili tribe: one religious figure, one traditional/traditional leader, and one community figure. The research results show that the Kaili tribe has peaceful values as the basis for building a culture of peace. The peaceful values possessed by the Kaili tribe are found in the philosophy of Nosarara Nosabatutu, including 1) Respecting human values (Membahargai nilai nu manusia); 2) Empathy towards others (Nombarasai nuapa nirassaintora); 3) Helping each other (mositulungi ante todea); 4) Deliberation to reach a consensus (Molibu mompaka sangu); 5) Caring for others  (Merasai nuapa nirasaintona); dan 6) Protecting nature (Mojagai tongrafa).